The Coupling Effect of Pore Water Pressure and Pore Water Gravity in Unsaturated Soils under Rainfall Condition and Its Influence on Slope Stability. (22nd October 2022) - Zhao, Nenghao; Lu, Haijun; Zhang, Rongtang
Abstract : In the study of the impact of rainfall on the unsaturated soil slope, the changes of pore water pressure and effective stress are frequently analyzed, while the loading effect caused by the change of pore water content in unsaturated soils is often neglected. In order to realize the coupling effect of the above two, a coupling model involving pore water pressure and pore water gravity was established based on the principle of seepage-stress coupling in unsaturated soils. Through a case verification, the coupling effect of pore water pressure and pore water gravity on the unsaturated soil slope was analyzed from the aspects of effective saturation, pore water pressure, effective stress, displacement, and stability. At the same time, the results were compared with those considering only the pore water pressure. The results show that the slope stability is relatively poor considering the coupling of unsaturated pore water pressure and pore water gravity. Therefore, the gravity effect of pore water in unsaturated soils cannot be neglected when calculating the stability of unsaturated soil slope under rainfall condition.